Restaureringens effekt på öringpopulationen - Carlström, Ola; Dagman, Sebastian (2022)
Until the 1970s, rivers in Sweden were used for timber floating. In order for the floating to be as efficient as possible, with a minimum of timber getting stuck, many rivers were cleared. Large rocks and boulders were removed from the main channel and tributaries, backwaters and shallow areas were secluded. This meant that the current increased in the main channel and became more homogeneous. Additional effects of the clearing were increased transport of sediment, increased bottom ice formation and poorer conditions for reproduction and survival for insects and fish. Restoration is a method used to restore the structure of watercourses. The goal is to achieve a heterogeneous structure in terms of e.g. depth, current conditions and substrate. Through restoration, habitats and spawning grounds can be created for trout. The aim of this study is to examine the effects of restoration on the trout population. The trout stocks were inventoried with the help of electric fishing as the population can be estimated and followed over time at the same location. The watercourses that have been studied are 6 tributaries to the Vindel river: Beukabäcken, Giertsbäcken, Nackbäcken, Olsbäcken, Ruskträskbäcken and Storkvarnbäcken. The results of the restoration show a significant difference in population density between the creeks and over time for 0+ trout. For >0+ trout, no significant difference in population density between the creeks or over time is found. How the trout population develops after a restoration highly depends on what the population looked like before the restoration. The conclusion is that the restoration has a positive effect on parts of the trout population, but it takes time before the fish establish themselves.